Reed Membrane as a Novel Immobilization Matrix for the Development of an Optical Phenol Biosensor - Li, Yongjin (Current Analytical Chemistry, 2020)
Background: Biocompatible and easily available immobilization matrix is vital for the construction of enzyme-based biosensor. Methods: Reed membrane was selected as a novel immobilization matrix to construct an optical phenol biosensor. Tyrosinase from mushroom was immobilized in a reed membrane using glutaraldehyde as a cross-linker. The detection scheme was based on the measurement of the color intensity of the adduct resulting from the reaction of 3-methyl-2-benzothiazolinone hydrazone (MBTH) with the quinone produced from the oxidation of phenol by tyrosinase. The performance of such method including specificity, sensitivity, repeatability and practical use were validated. Results: The prepared biosensor demonstrated optimum performance at pH 6-7, temperature of 40°C and a linear response in the phenol concentration range of 5-100 μM. It also showed good operation stability for repeated measurements (over 200 times) and good storage stability after it had been kept at 4°C for 2 months. Conclusion: Reed membrane is a novel matrix for immobilization of enzyme. The prepared biosensor permits good sensitivity, reproducibility and stability. It is anticipated that reed membrane is a promising solid support for fabricating other enzyme-based biosensors.
Keywords: tyrosinase